The Role of The Islamic Conference Organization and Expectations of The Future Role - Mubarok, Abdullah; Bahri, Efri Syamsul; Aslam, Mohd Mizan Mohammad (Indo Consultan Energi, 2024)
The Organization of the Islamic Conference (OIC) is the foundation of Muslims in various dimensions of life. This research aims to identify the role of OIC globally. This research uses qualitative methods with a descriptive approach and a literature study. Research reference data was obtained from journals and reference books related to the role of the OIC. The study's results found ten dimensions of the OIC's role globally: politics, tourism, Islamic diplomacy, conflict resolution, humanity, cooperation for development, human rights, Islamic finance, world peace, and the development of science and technology. The OIC, as an association of countries with an Islamic background, needs to increase its role globally as a solution to various dimensions of problems experienced by OIC members. The implication is that in the future, we need to play an optimal role in population, poverty alleviation, finance, Islamic microfinance, halal economy, humanity and human resources.